Nicotine replacement therapy for smoking cessation. - Stead, L; Perera, R; Bullen, C; Mant, D; Lancaster, T (2008)
BACKGROUND: The aim of nicotine replacement therapy (NRT) is temporarily to replace much of the nicotine from cigarettes to reduce motivation to smoke and nicotine withdrawal symptoms, thus easing the transition from cigarette smoking to complete abstinence. OBJECTIVES: The aims of this review were:To determine the effect of NRT compared to placebo in aiding smoking cessation, and to consider whether there is a difference in effect for the different forms of NRT (chewing gum, transdermal patches, nasal spray, inhalers and tablets/lozenges) in achieving abstinence from cigarettes. To determine whether the effect is influenced by the dosage, form and timing of use of NRT; the intensity of additional advice and support offered to the smoker; or the clinical setting in which the smoker is recruited and treated. To determine whether combinations of NRT are more likely to lead to successful quitting than one type alone. To determine whether NRT is more or less likely to lead to successful quitting compared to other pharmacotherapies. SEARCH STRATEGY: We searched the Cochrane Tobacco Addiction Group trials register for papers with 'nicotine' or 'NRT' in the title, abstract or keywords. Date of most recent search July 2007. SELECTION CRITERIA: Randomized trials in which NRT was compared to placebo or to no treatment, or where different doses of NRT were compared. We excluded trials which did not report cessation rates, and those with follow up of less than six months. DATA COLLECTION AND ANALYSIS: We extracted data in duplicate on the type of participants, the dose, duration and form of nicotine therapy, the outcome measures, method of randomization, and completeness of follow up. The main outcome measure was abstinence from smoking after at least six months of follow up. We used the most rigorous definition of abstinence for each trial, and biochemically validated rates if available. We calculated the risk ratio (RR) for each study. Where appropriate, we performed meta-analysis using a Mantel-Haenszel fixed-effect model. MAIN RESULTS: We identified 132 trials; 111 with over 40,000 participants contributed to the primary comparison between any type of NRT and a placebo or non-NRT control group. The RR of abstinence for any form of NRT relative to control was 1.58 (95% confidence interval [CI]: 1.50 to 1.66). The pooled RR for each type were 1.43 (95% CI: 1.33 to 1.53, 53 trials) for nicotine gum; 1.66 (95% CI: 1.53 to 1.81, 41 trials) for nicotine patch; 1.90 (95% CI: 1.36 to 2.67, 4 trials) for nicotine inhaler; 2.00 (95% CI: 1.63 to 2.45, 6 trials) for oral tablets/lozenges; and 2.02 (95% CI: 1.49 to 3.73, 4 trials) for nicotine nasal spray. The effects were largely independent of the duration of therapy, the intensity of additional support provided or the setting in which the NRT was offered. The effect was similar in a small group of studies that aimed to assess use of NRT obtained without a prescription. In highly dependent smokers there was a significant benefit of 4 mg gum compared with 2 mg gum, but weaker evidence of a benefit from higher doses of patch. There was evidence that combining a nicotine patch with a rapid delivery form of NRT was more effective than a single type of NRT. Only one study directly compared NRT to another pharmacotherapy. In this study quit rates with nicotine patch were lower than with the antidepressant bupropion. AUTHORS' CONCLUSIONS: All of the commercially available forms of NRT (gum, transdermal patch, nasal spray, inhaler and sublingual tablets/lozenges) can help people who make a quit attempt to increase their chances of successfully stopping smoking. NRTs increase the rate of quitting by 50-70%, regardless of setting. The effectiveness of NRT appears to be largely independent of the intensity of additional support provided to the individual. Provision of more intense levels of support, although beneficial in facilitating the likelihood of quitting, is not essential to the success of NRT.